PENGARUH MOTIVASI DAN KEPEMIMPINAN SERTA PENGEMBANGAN KARIR TERHADAP OCB MELALUI KOMITMEN ORGANISASI DAN KEPUASAN KERJA PADA MANAJER PERUSAHAAN SWASTA DI SURABAYA - H.Teman Koesmono (Journal of Management and Business, 2006)
The purpose of this research is to find out the effect of Motivation, Leadership and Career Development on Organization Citizenship Behavior pass through Organization Commitment and Job Satisfaction. This research’s object is manajer’s private company in Surabaya. The result of the research can explain that Motivation, Leadership, Career Development, Job Satisfaction and Organization Commitment affect to Organization Citizenship Behavior of managers. Manager's position is important for company obyective.The more positive manager's behavior they get hopefully the faster the company,s short/long term goal will be achieved. Along with the achievement the company's goal there will be an affect on improvement of manajer's working satisfaction and welfare.